Kewenangan Otoritas Jasa Keuangan Dalam Pengaturan dan Pengawasan Di Sektor Perbankan - Hirsanuddin -; Muhaimin -; Ari Rahmad Hakim BF; Yudhi Setiawan (Jatiswara, 2016)
Indonesian Bank authority to regulate and supervise the banking sector authorities are granted by the authority of attribution that the authority granted by law, namely Law No. 21 Year 2011 on the Financial Services Authority. But the authority given the nature of Persia, because the authority of Bank Indonesia in conducting the examination and supervision of the bank, Bank Indonesia pemeriksannya results are not given the authority to assess the results of the examination itself, but should be reported to the Financial Services Authority. The authority of the Financial Services Authority in the conduct regulation and supervision by the authority of attribution that the authority granted under Act No. 21 of 2011 on the Financial Services Authority carry out the task of supervising and regulating the activities of financial services in banking sector, the activities of financial services in the capital markets sector and service activities finance in the insurance sector, pension funds, financial institutions, and other financial institutions.